Common Mistakes Faced by Student Indonesian to English Simultaneous Interpreting - Regina Immaculata (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2022)
Abstract A lot of people seem to be unaware of the difference between interpreter and translator. Different practices lead to different skills. This study aims to find common mistakes that are often made by students in interpreting. The data were obtained from five students who had undergo interpreting classes for one year from 2020 January until December. These five Master degree students attended the interpreting class 32 times with a total study time of 90 hours. The data were taken in an online class, after that this study analyze transcripts, validate errors, and interview students. The study found that the most common mistakes were hestitations and omissions. These mistakes are caused by several factors, namely nervous and time pressure, lack of background knowledge and lack of language proficiency, as well as poor network connection and environmental noise Keywords: errors; Indonesia to English simultaneous interpreting, problem in simultaneous interpreting   Abstrak Banyak orang yang belum mengetahui perbedaan penerjemah dan penjurubahasa, padahal pekerjaan yang berbeda memerlukan kemampuan yang berbeda. Penelitian ini bertujuan untuk menemukan kesalahan umum yang sering dilakukan mahasiswa yang mempelajari penjurubahasaan. Data diperoleh dari lima mahasiswa yang telah mengikuti kelas penjurubahasaan selama satu tahun dari Januari sampai Desember 2020. Lima mahasiswa ini menghadiri kelas jurubahasa sebanyak 32 kali dengan total waktu belajar 90 jam. Penelitian ini menerapkan metode kualitatif dengan menganalisis transkrip, melihat validasi kesalahan, dan mewawancara murid. Studi ini menemukan bahwa kesalahan yang paling umum dilakukan adalah keraguan dan penghapusan. Kesalahan ini disebabkan beberapa faktor yaitu keraguan dan tekanan waktu, kurangnya pengetahuan umum dan kemampuan berbahaasa asing, serta jaringan internet yang buruk dan lingkungan yang bising. Kata Kunci: kesalahan, interpreter simultan Bahasa Inggris- Bahasa Indonesia, permasalahan dalam interpreter simultan